Pragmatic and Progressive Legal Practice: Ethnographic Case Study of Jatigede Reservoir - Teddy Asmara (Jurnal Dinamika Hukum, 2022)
This study reveals the legal method in the process of land compensation in the Jatigede reservoir, and focuses on: the existence and application of pragmatic law by rural farming communities; and the government's use of progressive law. By using a combination of case study and micro-ethnographic methods, the answers are obtained, first, the pragmatic legal character is relatively in line with speculative cognition and defensive principles; its adaptive application is to resist the law silently, and the aggressive one is to violate the law openly. Second, the government understands the manipulation of compensation as a reflection of the accumulated injustice and economic difficulties of the citizens, therefore the government makes regulations that prioritize the restoration of people's welfare rather than fulfilling the requirements of legal logic.Keywords: people's welfare; speculative cognition; compensation manipulation; defensive principle; ethnographic-case study